Putative effects of moringa oil or its nano-emulsion on the growth, physiological responses, blood health, semen quality, and the sperm antioxidant-related genes in ram - Rehab F. S. A. Ismail; Wael A. Khalil; Sara I. Grawish; Karima Gh. M. Mahmoud; Sameh A. Abdelnour; Alaa M. A. Gad (BMC Veterinary Research)
Abstract Phytochemicals have been effectively used to enhance the growth and productivity of farm animals, while the potential roles of essential oils and their nano-emulsions are limited. This plan was proposed to investigate the impacts of orally administered moringa oil (MO) or its nano-emulsion (NMO) on the growth, physiological response, blood health, semen attributes, and sperm antioxidant-related genes in rams. A total of 15 growing Rahmani rams were enrolled in this study and allotted into three groups. The 1st control group received a basal diet only and treated orally one mL of distilled water, while the 2nd, and 3rd groups received a basal diet and were orally treated with 1 mL of NMO or 2 mL of MO /head/day for 4 months, respectively. Growth, physiological response, blood health, semen quality, and antioxidant genes in sperm were assessed. The MO and NMO treatments had no significant effect on growth indices (final body weight and weight gain ) and physiological response (rectal temperature, pulse, and respiration rates) (P > 0.05). The NMO group had the lowest levels of MCV (mean corpuscular volume) (P < 0.05), while all treated groups produced higher levels of mean corpuscular hemoglobin (MCH) and mean corpuscular hemoglobin concentration (MCHC) compared to those in the control group (P < 0.05). Aspartate transferase (AST) and total cholesterol were significantly reduced in the MO and NMO groups, while total protein and glucose levels were significantly improved in NMO group (P < 0.05). Serum and seminal interstitial-cell-stimulating hormone (ICSH) levels were significantly improved (P < 0.0001) in the NMO group. Testosterone in serum and seminal plasma was significantly improved (P < 0.0001) in the MO group. Total antioxidant capacity (TAC) levels showed a tendency to increase in both the MO and NMO groups, but this increase was not significant compared to the untreated group (P > 0.05). On the other hand, the MO group exhibited lower levels of AST and malondialdehyde (MDA), while the alanine aminotransferase (ALT) levels were the lowest in the NMO group (P > 0.05). Mass motility, viability, membrane integrity and sperm concentration were significantly improved in the MO group (P < 0.0001) compared to the other groups. The NMO group had worse expressions of superoxide dismutase 1 (SOD1) compared to the control and MO groups. MO group significantly upregulated the catalase gene compared to the other groups (P < 0.001). The expression of Caspase-3 was highest in the group that received NMO compared to the other groups (P < 0.001). This study suggests that MO may serve as a novel therapeutic agent for improving the reproductive health in Rahmani rams.